Synthesis and luminescence of graphene-nano calcium sulphide composite - Sharma, Geeta; Patil, K. R.; Gosavi, S. W. (Materials Chemistry and Physics, 2014)
Graphene-nanocrystalline calcium sulphide has been synthesized using in-situ reduction of calcium salt and graphene oxide. Graphene oxide was prepared using Hummer's method. Surface morphology and crystal structure of samples were observed by transmission electron microscopy (TEM) and X-Ray diffraction (XRD). Ultra thin graphene and graphene oxide sheets with size ranging between tens to several hundreds of square nanometers are observed in TEM images. The TEM micrographs of G-CaS show that CaS particles are embedded in graphene sheets and the average particle size of CaS particles in the composite is less than 50 nm. The reduction in the intensity of various functional groups in FTIR spectrum also confirms the formation of graphene. The UV-Visible spectra of CaS shows absorption peak at 220 nm with a small shoulder at 250 nm whereas in G-CaS 220 nm absorption peak has reduced intensity and the shoulder at 250 nm has now shifted to 270 nm due to modification in the defect structure of CaS by graphene. CaS and G-CaS shows photoluminescence emission at 470 nm (lambda(exc.) = 375 nm) and 440 nm (lambda(exc.) = 350 nm) respectively, however emission intensity of G-CaS is relatively lower than CaS. Although the emission intensity is found to be lower than CaS, addition of CaS to graphene in G-CaS complex has made graphene luminescent. XPS spectra also indicate reduction of various oxygen containing functional groups in highly reduced graphene oxide and G-CaS. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Luminescence; Nanostructures; powder diffraction; Precipitation

Synthesis of graphene from activated carbon at liquid nitrogen temperature and its detailed structural analysis - Sharma, Preeti; Sharma, Geeta; Punia, Rajesh (Applied Physics A-Materials Science & Processing, 2021)
The present study deals with the synthesis of graphene using thermal quenching of pre-heated activated carbon (a-C) (1370 K for 3 h) at liquid nitrogen temperature and its detailed structural analysis using XRD, TEM, FTIR and Raman spectroscopy. The analysis of lattice parameters (L-a, L-c,L- and d) of constituent nanographitic domains using XRD shows restoration of graphene-like structure in the resultant product (a-CL). TEM image reveals porosity and partially crystallinity (from SAED) in a-C. While thin layers of graphene are observed in the TEM images of a-CL Deconvoluted Raman spectra have been used to investigate the evolution of crystalline behaviour of a-C with temperature in view of Ferrari and Robertson's three-stage model. The evolution of G peak and increase in I-D/I-G reveals restoration of crystallinity in a-CL. The development of the D peak indicates disordering of graphite but ordering of amorphous carbon. The reported method is technologically beneficial for graphene synthesis for large number of applications such as supercapacitors, H-2 storage, gas separation and purification.
Keywords: activated carbon; Amorphous carbon; graphene; H-2 storage applications; Raman spectroscopy; Supercapacitors